Control of drying shrinkage in magnesium silicate hydrate (m-s-h) gel mortars. (October 2016) - Zhang, Tingting; Liang, Xiaomin; Li, Changming; Lorin, M.; Li, Yanying; Vandeperre, Luc J.; Cheeseman, Chris R.
Abstract: Magnesium silicate hydrate (M-S-H) gel can be formed by the reaction of MgO with amorphous silica in the presence of sodium hexametaphosphate (Na-HMP). Typical pastes contain 40% MgO and 60% SF and have a w/c ratio of 0.5, but these exhibit shrinkage cracking on drying. The shrinkage characteristics of M-S-H mortar samples containing different additions of sand have been studied using dilatometry. The drying shrinkage was found to decrease with increasing sand addition and to increase with increased water content. Mortars with 60 wt.% sand addition and a w/c ratio of 0.5 had a drying shrinkage of 0.16% and did not show shrinkage cracking. A simple geometrical model based on particle packing is presented that explains the observed changes in drying shrinkage. Based on the geometrical model, the shrinkage of M-S-H mortar system can be reduced to zero when the volume fraction of sand in the mortar is about 0.77.